Protective Effect of Bixin Isolated from Bixa orellana L. Seeds on UVB-Induced Inflammation and Immunosuppression of the Skin (Bangladesh Journal of Medical Science, 2018)
Background: DNA damage caused by excessive ultraviolet B (UVB) radiation on the skin triggers the response to inflammatory and immunosuppression. The bixin from Bixa orellana L. has been proven to be able to inhibit cyclo-oxygenase.Objective: to verify whether the bixin lotion has the effect to offer protection against inflammation and immunosuppression due to acute UVB irradiation in shaved BALB /c mice.Methods: Protection against inflammation and immunosuppression, respectively were studied in 4 groups of mice. Each group was treated respectively with topical application of base lotion as a control; bixin lotion doses of 0.5 mg; 2.5 mg and 125 mg, for 10 days prior to and during the UVB irradiation. The Inflammation was induced by UVB irradiation, 360 mJ/cm2 once a day for 3 consecutive days, whereas the immunosuppression was induced by UVB irradiation, 360 mJ/cm2 once a day for 5 consecutive days. The inflammatory response was measured as an increase in middorsal skinfold thickness at the peak response. The immune response was measured as the contact hypersensitivity (CHS) response to oxasolon sensitization.Results: The results indicated that in concentration range used, bixin lotion significantly decreased the middorsal skinfold thickness at 72 hours after UVB radiation (p